Computer Experiments on Rapidly Rotating Plane Couette Flow (Communications in Computational Physics, 2010)
The turbulence in plane Couette flow subjected to system rotation is investigated.The anti-cyclonic rotation rate is well above the range in which roll-cells occurand close to the upper bound, beyond which no stationary turbulent states of motionexist. The mean velocity profile exhibits a linear region over 80% of the cross-section, inwhich the mean absolute vorticity is driven to zero. Viscous effects still prevail in narrowregions next to the walls, whereas the quasi-homogeneous central core exhibitsabnormal anisotropies of the Reynolds stress tensor, the vorticity tensor and the energydissipation rate tensor. In spite of the distinctly higher turbulence level observed,a 13% drag reduction is found. This paradoxical finding is ascribed to configurationalchanges in the turbulence field brought about by the system rotation.